Η Carinae: high angular resolution continuum, H30α and He30α ALMA images. Issue 2 (23rd September 2020) - Abraham, Zulema; Beaklini, Pedro P B; Cox, Pierre; Falceta-Gonçalves, Diego; Nyman, Lars-Åke
ABSTRACT: We present images of η Carinae in the recombination lines H30α and He30α and the underlying continuum with 50 mas resolution (110 au), obtained with ALMA. For the first time, the 230 GHz continuum image is resolved into a compact core, coincident with the binary system position, and a weaker extended structure to the NW of the compact source. Iso-velocity images of the H30α recombination line show at least 16 unresolved sources with velocities between −30 and −65 km s −1 distributed within the continuum source. A NLTE model, with density and temperature of the order of 10 7 cm −3 and 10 4 K, reproduce both the observed H30α line profiles and their underlying continuum flux densities. Three of these sources are identified with Weigelt blobs D, C, and B; estimating their proper motions, we derive ejection times (in years) of 1952.6, 1957.1, and 1967.6, respectively, all of which are close to periastron passage. Weaker H30α line emission is detected at higher positive and negative velocities, extending in the direction of the Homunculus axis. The He30α recombination line is also detected with the same velocity of the narrow H30α line. Finally, the close resemblance of the H30α image with that of an emission line that was reported in the literature as HCO + (4–3) led us to identify this line as H40δ instead, an identification that is further supported by modelling results. Future observations will enable to determine the proper motions of all the compact sources discovered in the new high angular resolution data of η Carinae.